Investigating the economic case of a service to support carers of people with dementia: A cross‐sectional survey‐based feasibility study in England. (21st June 2019) - Longo, Francesco; Faria, Rita; Parker, Gillian; Gridley, Kate; Aspinal, Fiona; Van den Berg, Bernard; Weatherly, Helen
Abstract: Carers contribute essential support to enable people with dementia to continue living within the community. Admiral Nurses provide specialist dementia support for carers of people with dementia, including offering expert emotional support and guidance, and work to join up different parts of the health and social care system to address needs in a co‐ordinated way. The cost‐effectiveness of this service is not clear. We undertook a feasibility study to explore related outcomes and costs for these carers. A cross‐sectional, clustered survey was undertaken in England in 2017, in areas with and without Admiral Nursing (AN). The survey questionnaire included questions on the characteristics of the carers and the person with dementia, outcomes (care‐related quality of life [CRQoL], self‐efficacy and subjective well‐being), use of health and social care services, out‐of‐pocket costs and time spent on informal care. We used different econometric techniques to compare the outcomes and the costs of the carers with and without AN services: linear regression, propensity score matching and instrumental variables analysis. These techniques allowed us to control for differences in observed and unobserved characteristics between the two groups of carers which determined outcomes and costs. We concluded that AN services might have a positive effect on carers' CRQoL, self‐efficacy and subjective well‐being. Furthermore, we found little difference in costs between carers using AN and those using usual care, or in the costs of the people with dementia they care for. Our findings provided an initial indication as to whether AN services could be good value for money. The key limitation of the study was the difficulty in controlling for unobserved characteristics because of the cross‐sectional nature of our observational data. To diminish this limitation, our survey could be used in future studies following carers with and without AN services over time.